'Aristocystites? subcylindricus var. de bohemicus Barrande, 1887' is a valid species of Aristocystites (Echinodermata, Diploporita): description and taxonomic consequences. (17th April 2019) - Paul, Christopher R.C.; Parsley, Ronald L.
Abstract: Barrande erected the genus Aristocystites, type A. bohemicus Barrande, in 1887. He listed other questionable species, including " A. ? subcylindricus var. de bohemicus. " Aristocystites subcylindricus has not been accepted apart from Bather who in 1919 designated a type specimen and made it the type species of the new genus Hippocystis . No specimens available to Barrande or Bather preserved the oral area necessary to characterize Hippocystis or A. subcylindricus . Specimen 436969A, in the United States National Museum of Natural History is a more complete specimen of A. subcylindricus and preserves the oral area. This shows that A. subcylindricus is a valid species, but has two ambulacral facets, a character unique to the genus Aristocystites . Aristocystites subcylindricus has tumid plates with obvious sutures, a rounded thecal base, and a gonopore surrounded by three plates. Aristocystites bohemicus has smooth plates, an obvious attachment scar aborally and a gonopore within a single plate. Both species have occasional horseshoe-shaped diplopores. UUID:http://zoobank.org/946c28a2-5783-4a6b-9111-416857bf9363